Limiter removal: fitness tracking mobile application - Muhammad Asyraf, Rahman (2019)
For decades the war on creating a healthy society goes on and is predicted not to end anytime soon. Solutions after solutions have been presented to the world but the task just gets harder as the environments change. Parallel to the increase of difficulty to the problem the massive increase in technology development have set a new resolution for mobile application engineers to invest in promoting health. What exists in this thesis includes a project that promotes self-wellbeing through exercise and advice to increase health. This project uses the fact that it is easier to give guidance to individuals with what a person spends their time the most with which is the smartphone. The aspects most highlighted in this project is the network on applying a server and how a server client relationship eases in assisting the mobile application. As a networking student we found after years of practice that the right networking model will increase the efficiency of running a mobile application.